Talagrand’s Inequality and Locality in Distributed Computing - Dubhashi, Devdatt P. (BRICS Report Series, 1998)
We illustrate the use of Talagrand’s inequality and an extension of it to dependent random variables due to Marton for the analysis of distributed randomised algorithms, specifically, for edge colouring graphs.